Effect of Inclusion Corn Distillers’ Dried Grains with Soluble on Performance, Carcass and Meat Quality on Broiler Chicken - Majdi Abdelfaraj Kairalla; Idris Alshelmani, Mohamed; Imdakim Mohamed Muftah; Abdalhakim Amer Aburas (Zanco Journal of Pure and Applied Sciences, 2025)
Evaluating the impact of adding distillers' dried grains with solubles (DDGS) on broiler performance was the aim of the current experiment. A total of 240 one-day-old broiler chicks (Ross 308) were obtained from a local hatchery and divided into four dietary treatments randomly. There were four replicates of each treatment, fifteen birds per replicate. In broiler diets, DDGS was added at percentages of 0%, 10%, 20%, and 30% DDGS. At day 42, one bird per replication was selected to examine blood biochemistry, carcass traits, and meat quality. The findings showed that the group of birds fed a 20% DDGS considerably (P<0.05) improved the growth performance and feed conversion ratio (FCR) compared to the other groups. In addition, the birds fed DDGS basal diets were considerably (P<0.05) lower in total cholesterol, triglycerides and LDL compared to the control. The inclusion of 30% DDGS led to decreased broiler performance and carcass yield. In conclusion, the DDGS can be fed to the broilers up to 20% without adverse effects on growth performance.